2023
DOI: 10.5694/mja2.51906
|View full text |Cite
|
Sign up to set email alerts
|

Universal genetic testing for women with newly diagnosed breast cancer in the context of multidisciplinary team care

Abstract: Objective To determine the feasibility of universal genetic testing of women with newly diagnosed breast cancer, to estimate the incidence of pathogenic gene variants and their impact on patient management, and to evaluate patient and clinician acceptance of universal testing. Design, setting, participants Prospective study of women with invasive or high grade in situ breast cancer and unknown germline status discussed at the Parkville Breast Service (Melbourne) multidisciplinary team meeting. Women were recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
(47 reference statements)
1
6
0
Order By: Relevance
“…Similarly, De Silva et al found that in a cohort of Australian patients with breast cancer, universal GGT resulted in changes in clinical management for 77% of individuals. 48 Of note, VUS were not reported to patients in this study to avoid anxiety, unnecessary treatments, and undue burden on cancer clinics. Although VUS were reported in our study, nondisclosure of VUS may be an attractive option, especially for nongenetics providers implementing universal GGT.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Similarly, De Silva et al found that in a cohort of Australian patients with breast cancer, universal GGT resulted in changes in clinical management for 77% of individuals. 48 Of note, VUS were not reported to patients in this study to avoid anxiety, unnecessary treatments, and undue burden on cancer clinics. Although VUS were reported in our study, nondisclosure of VUS may be an attractive option, especially for nongenetics providers implementing universal GGT.…”
Section: Discussionmentioning
confidence: 81%
“…A number of studies have demonstrated that current guidelines miss patients with actionable PGVs, preventing them from receiving genetics-informed care. 22 , 37 , 42 , 47 , 48 It has been suggested that GGT results may result in deviation from management guidelines. In 20,568 women with BC who underwent GGT, Kurian et al found that women with PGVs in BC predisposition genes were more likely to overuse BLM and chemotherapy and to underuse RT compared with patients with negative results.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in Australia, where mainstreaming of genetic testing and counselling has removed cost as a major impediment, a considerable proportion of women are unable to get tested due to the extremely stringent eligibility criteria. The Mutational Assessment of newly diagnosed breast cancer using Germline and tumor genomICs (MAGIC) study found that 31 out of 474 study participants were carriers of pathogenic variants in cancer-associated genes ( 13 ). However, 18 out of those 31 participants would be ineligible for routine genetic testing per the local testing guidelines ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…While cost is not a significant barrier to testing in Australia due to mainstreaming of genetic testing for several breast cancer genes, the restrictive eligibility criteria result in a considerable proportion of at-risk women not receiving the benefits of genetic testing and counselling ( 12 , 13 ). Absence of a clear family history due to sociocultural factors also contributes to limited uptake of genetic testing and counselling in Australia.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on universal testing indicate that guidelines should be broadened to encompass testing of all patients diagnosed with BC ( 65 – 67 ). Researchers report that universal genetic testing after BC diagnosis can uncover clinically significant germline pathogenic variants that might otherwise escape detection due to narrow selection criteria as per current testing guidelines ( 66 ).…”
Section: Management Of Brca -Mutated Early-stage B...mentioning
confidence: 99%